ANALISIS TINGKAT KEPUASAN PELANGGAN JASA INTERNET - Samboro, Drs. Joko (Fakultas Ekonomi, UIN Maliki Malang, 2008)
This research analisys to find out the degree of customers’ satisfaction and to give informations to the management to direct customers’ need in order to achieve customers’ satisfactioan. To collect the data,the purposive sampling is applied in this research 90 guestionaires are distributed togo respondents and then they are analyzed by using the window of satisfaction on the cartecius diagram The result of the research indicates that mostof the cuatomers are not satisfied, the degree of their satisfactions is less than 100%. Further, some service items available in the firm are stiil low. The researcher hopes the result of this research is able to give the information to the firm’s leader in finding out the effective strategy in geeting more customers.